Conservatism, the Right Wing, and the Far Right [four-volume set] : a Guide to Archives. - Henderson, Archie (Ibidem Press, 2018)
This unique collection is the essential guide to archival research on conservatism, the right wing, and the far right, offering a detailed overview of primary sources including documents, film, video, sound recordings, microfilm and microfiche, cartoons, sheet music, newspaper art, and more in more than 4500 archives across twenty-two countries.